Segmentasi Citra Kartu Pias Tipe SO-40U (1400-40S) Pada Perhitungan Lama Penyinaran Matahari - Pujiastuti, Asih (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2017)
The measurement of the duration of solar irradiation at the climatology station can be done using campbell stokes and pias cards. The aim of this research is to assist the climatology station operator to determine the burn object on the SO-40U (1400-40S) type of pias cards, making it easier to calculate the duration of solar irradiation. This app is designed and built to successfully segmentation the burn on the card automatically. In this research, the data was collected at a climatology station located in Barongan, Sumberagung Jetis, Bantul. Based on the test conducted segmentation generated in this study is good and produce RMSE number of object result of segmentation equal to 2,6485 to sum object in original image. The difference in object calculation results from a segmentation error caused by a small burning object of the pias card and or a thin but translucent object, so that the object is partially lost or forms an objects separation area.